Association of neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, and De Ritis ratio with mortality in renal cell carcinoma: A multicenter analysis - Keiner, Cathrine; Meagher, Margaret; Patil, Dattatraya; Saito, Kazutaka; Walia, Arman; Liu, Franklin; Dutt, Raksha; Miller, Nathan; Dhanji, Sohail; Saidian, Ava; Wan, Fang; Yasuda, Yosuke; et al. (Frontiers in Oncology, 2022)
Background Several markers of inflammation have been associated with oncologic outcomes. Prognostic markers are not well-defined for renal cell carcinoma (RCC). We sought to investigate the association of preoperative neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and De Ritis ratio with mortality in RCC. Methods Multi-center retrospective analysis of patients undergoing surgery for RCC. Primary outcome of interest was all-cause mortality (ACM). Secondary outcomes were non-cancer mortality (NCM) and cancer-specific mortality (CSM). Elevated NLR was defined as ≥2.27, elevated PLR as ≥165, and elevated De Ritis ratio as ≥ 2.72. Multivariable cox regression analysis (MVA) was conducted to elucidate risk factors for primary and secondary outcomes, and Kaplan-Meier analysis (KMA) was used to evaluate survival outcomes comparing elevated and non-elevated NLR, PLR, and De Ritis ratio. Results 2656 patients were analyzed (874 patients had elevated NLR; 480 patients had elevated PLR and 932 patients had elevated De Ritis). Elevated NLR was a significant predictor of ACM (HR 1.32, 95% CI: 1.07-1.64, p=0.003) and NCM (HR 1.79, 95% CI: 1.30-2.46, p<0.001) in MVA. Elevated De Ritis was a significant predictor of ACM (HR 2.04, 95% CI: 1.65-2.52), NCM (HR 1.84, 95% CI: 1.33-2.55, p<0.001), and CSM (HR 1.97, 95% CI:1.48-2.63, p<0.001). KMA revealed significant difference in 5-year overall survival (OS) (48% vs. 68%, p<0.001), non-cancer survival (NCS) (69% vs. 87%, p<0.001), and cancer-specific survival (CSS) (60% vs. 73%, p<0.001) for elevated versus non-elevated NLR. For PLR, there was a difference in 5-year OS (51% vs. 61%, p<0.001) and CSS (60% vs. 73%, p<0.001) with KMA. Conclusions Elevated NLR was independently associated with worse ACM and NCM, while elevated De Ritis was predictive for CSM in addition to ACM and NCM. These differences may be useful in refining risk stratification with respect to cancer-related and non-cancer mortality in RCC patients and deserve further investigation.